Immunochemical characterization of Micrurus nigrocinctus nigrocinctus venom with monoclonal and polyclonal antibodies - Alape Girón, Alberto (1994)
Eleven murine monocloncal antibodies (MAbs) against Micrurus nigrocinctus nigrocinctus venom were produced and partially characterized. When M. n. nigrocinctus venom proteins were separated by SDS-PAGE under non-reducing conditions four sharp and three diffuse bands were observed. The sharp bands had migration rates comparable to reduced standards of 10, 12, 50 and 72 kDa. The diffuse bands migrate in the range of reduced standards from 14.5 to 32 kDa. When venom proteins were separated under reducing conditions the same sharp bands and an additional prominent 14.5 kDa band were observed. Three antibodies (MAbs 4, 21 and 28) recognized the diffuse bands in western blots of non-reducing SDS-PAGE, whereas MAbs 7G, 22 and 26 reacted with only the 72 kDa protein. MAbs 21 and 28 reacted with the 14.5 kDa band whereas MAb 7G recognized the 72 kDa band in blots of reducing SDS-PAGE. Two M. nigrocinctus antivenoms cross-reacted by ELISA against nine neurotoxic snake venoms, as well as with γ-toxin from Naja nigricollis and notexin. One antibody (MAb 9A) was used to affinity purify a fraction (called nigroxin) from M. n. nigrocinctus venom. Nigroxin showed phospholipase and myotoxic activities and appeared as a single 15 kDa band in SDS-PAGE under reducing conditions. However, three bands with slight differences in charge were resolved by urea-PAGE, representing isoforms named nigroxin a, b, and c. Nigroxin induced a dose-dependent release of peroxidase trapped in negatively charged liposomes. Nigroxin induced myonecrosis and increased the plasma creatine kinase levels in mice, when injected intramuscularly. The plasma membrane of cultured L6 myoblasts was permeabilized by nigroxin, as evidenced by the release of 3H-uridine nucleotides from prelabelled cells. This effect was completely abolished after preincubation with MAb 9A, although this antibody failed to neutralize the enzymatic activity of nigroxin. Nigroxin was also recognized by MAbs 4, 7H, 21, 27 and 28. Additionally, the epitope recognized by MAb 27 is also present in notexin and β-bungarotoxin.